Español - Lechón Sandoval, Juan Aníbal (2022)
Introduction: Child malnutrition is a prevalent problem at the world and national level that has been increasing over the years, the contribution of energy and other nutrients could contribute to improve this condition through the creation and development of easy-to-consume food products and versatile. Nutrition bars could be one of the options. Objective: To develop a nutritional bar as an alternative to combat child malnutrition. Methodology: A qualitative-quantitative experimental factorial study was carried out. Four treatments were carried out whose ingredient variations were made based on quinoa and oats compared to a control product. Proteins, fats and carbohydrates were determined, as well as the flavor profile. ANOVA analysis was run to study differences in the nutritional profile of the treatments. Results: Both energy, protein, fat and carbohydrates were significantly different between treatments (p <0.001). Treatment one made with 40% quinoa and 60% oats turned out to be the best option since it presented better shape, flavor, structure and size. Characteristics very similar to the control. Conclusion: Treatment one obtained better organoleptic and sensory characteristics, very similar to the control. It obtained a better nutritional profile with less carbohydrates and better fat and protein than the control, which is why it may be an option for consumption.